Daily Behavior of the Timor Deer (Cervus timorensis) at The Tahura of Wan Abdul Rachman Lampung of Tahura in Year 2021 - Maretta, Gres; Agustin, Karista Sandra; Putri, Claudia Tiara; Sofyan, Ichvan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The COVID-19 pandemic in Indonesia may affect changes in the daily behavior of the Timor deer in the Deer Captivity at the Grand Forest Park, Wan Abdul Rachman. The purpose of this study was to determine the daily behavior of the Timor deer (Cervus timorensis) during the COVID-19 pandemic at the Wan Abdul Rachman (WAR) Forest Park Deer Captivity (Tahura). The objects used are 4 male and female Timor deer. This study uses the Scan Sampling method with an interval of 10 minutes and starts from 08.00 - 17.00 WIB. Based on observations of the behavior of the Timor deer in captivity of the Tahura WAR Deer, it can be concluded that the most common behaviors are resting behavior (54.42%), eating behavior (34.95%), shifting behavior (6.37%), other behavior (2 ,6%), sleeping behavior (1,28%), self-playing behavior (0.79%) and social behavior (0.37%). During the COVID-19 pandemic (in 2021) there was an increase in the percentage of resting behavior (54.42%), sleeping (1.28%), social (0.37%), playing alone (0.79%) and others ( 2.6%) compared to the results of research before the covid-19 pandemic (in 2018) namely resting behavior (33.1%), sleeping (0.05%), social (0.26%), playing alone (0.6%) 1%) and others (2.45%). Meanwhile, the results of observations of the daily behavior of the Timor deer at the Tahura WAR Deer Captivity during the covid-19 pandemic (in 2021) showed a decrease in the percentage of eating behavior (34.95%) and moving (6.37%) compared to before the covid-19 pandemic (year). 2018) with the value of eating behavior (54.05%) and shifting behavior (9.99%). The difference in daily behavior shown to Timor deer in captivity is due to a decrease in the number of visitors due to the pandemic.